The endowment effect as blessing - Sivan Frenkel; Yuval Heller; Roee Teper (Bar-Ilan University, Department of Economics, 2017)
We study the idea that seemingly unrelated behavioral biases can coevolve if they jointly compensate for the errors that any one of them would give rise to in isolation. We suggest that the "endowment effect" and the "winner's curse" could have jointly survived natural selection together. We develop a new family of "hybrid-replicator" dynamics. Under such dynamics, biases survive in the population for a long period of time even if they only partially compensate for each other and despite the fact that the rational type's payoff is strictly larger than the payoffs of all other types.
Keywords: C73; D82; D03; 330; Endowment Effect; Winner's Curse; Bounded Rationality; Evolution